THE IMAGE OF GAREGIN NZHDEH IN ARMENIAN AND RUSSIAN COLLECTIVE MEMORY: SYMBOLIC CONFLICT IN URBAN SPACE (BASED ON RESEARCH IN ARMAVIR AND KRASNODAR) - Volhonskij, Mihail Alekseevic; Arlykapov, Ahmet Aminovic (History, Archeology and Ethnography of the Caucasus, 2022)
This article analyzes the symbolic aspects of the protracted conflict in Armavir between the city authorities and the leadership of Armavir branch of the Union of Armenians of Russia (from 2012 to 2019) in connection with the installation of a memorial plaque near the Armenian church in honor of the political figure Garegin Nzhdeh. The analysis of the conflict from the perspective of the concept of "symbolic politics" allowed us to identify some specifics of the policy of remembrance carried out by the Armenian diaspora in Russia. The conflict was caused by the different perception of Garegin Nzhdeh’s image in the Russian and Armenian cultural memory. For the collective memory of the Russian Armenians Nzhdeh is primarily a national hero, who fought for the independence of Armenia. In the Russian collective memory Nzhdeh is only a politician, who collaborated with the Nazi Germany during the Second World War. As the study showed, during the conflict Armenian and Russian activists used different kinds of memory policy strategies ("symbolic erasure", "symbolic camouflage" and "reformatting" of the previously created memorial space). The study also revealed some structural peculiarities of the collective, cultural and functional memory of Russian Armenians. In particular, the study showed that the collective memory of Russian Armenians has the character of an amalgam, which combines uncomplementary elements of Russian and Armenian collective, cultural memory.